Pathologic Findings in Rabbit Models of Hereditary Hypertriglyceridemia and Hereditary Postprandial Hypertriglyceridemia - Mitsuguchi, Yoko (American Association for Laboratory Animal Science, 2008)
In recent years, the association between hyperlipidemia and the development of arteriosclerosis has been addressed in several studies. Rabbit models of hypertriglyceridemia (TGH) and postprandial hypertriglyceridemia (PHT) have been developed at the authors' institute. TGH rabbits manifest pathology similar to that of humans with TGH, such as xanthoma, in addition to atherosclerosis of arterioles. Furthermore, PHT rabbits show visceral obesity, insulin resistance, and impaired glucose tolerance, with pathologic features similar to those of the metabolic syndrome assumed to be the cause of human ischemic heart disease. This study was designed to investigate the histopathologic features of TGH and PHT rabbits. TGH rabbits showed advanced aortic atherosclerosis, accompanied by intimal thickening of coronary and renal arteries, fatty liver changes, and xanthoma. PHT rabbits demonstrated aortic intimal thickening and hepatic fatty degeneration. The results of this study suggest that TGH and PHT rabbits are useful animal models for studying human hyperlipidemia and metabolic syndrome and the cardiovascular diseases that result from these conditions.